Acid microenvironments in microbial biofilms of antarctic endolithic microecosystems - Ríos, Asunción de los; Wierzchos, Jacek; Sancho, Leopoldo G.; Ascaso, Carmen (2003)
8 pages, and figures, and tables statistics. Antarctic endolithic microecosystems harbour distinct biofilms. The lithic substrate and the microorganisms comprising these films are intimately linked, leading to complex mineral–microbe interactions. Hence, the microhabitats and microenvironments of these microecosystems are not only determined by the physicochemical features of the lithic substrate, but are also conditioned by the biological components of these biofilms. The Antarctic biofilms analysed in this study are characterized by the presence of extracellular polymer substances and acid microenvironments in the proximity of the cells; cyanobacteria appearing as key components. On ultrastructural analysis, these endolithic cyanobacteria showed differences in sheath organization, probably related to their spatial position in the lithic substrate. It is proposed that in this type of ecosystem, biofilm structure could favour the formation of microsites with specific physicochemical conditions appropriate for the survival of microbial communities in this extreme environment. Peer reviewed